Properties and Novel Applications of Recycled Aggregates - Lopez Gayarre, Fernando (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The aggregates used in construction are the natural resource consumed the most in the world after air and water. Due to overexploitation, all environmental laws reward the use of recycled materials to guarantee the reduction of consumption of natural aggregates. The use of reclaimed aggregates, reused aggregates, and recycled aggregates increases sustainability in construction activities. Today, they are strategic materials in the manufacturing of green concrete and mortars and as road construction eco-efficient materials. In addition, the use of recycled aggregates from industrial or mining byproducts presents great potential in construction activities as recycled aggregates and/or supplementary cementitious materials. This Special Issue is open to new experiences in construction materials and/or works made with recycled aggregates.